2017
DOI: 10.2147/jpr.s139679
|View full text |Cite
|
Sign up to set email alerts
|

Pain aversion and anxiety-like behavior occur at different times during the course of chronic inflammatory pain in rats

Abstract: Pain is considered a multidimensional conscious experience that includes a sensory component and a negative affective-motivational component. The negative affective-motivational component of pain is different from the sensory component and amplifies the pain experience. Nowadays, a significant number of preclinical research groups have focused their attention on the affective symptoms of pain. In the present study, we investigated the pain aversion and anxiety-like behavior of the complete Freund’s adjuvant (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
3
26
1
2
Order By: Relevance
“…Like the anxiogenic effect of neuropathic pain (43, 44), CFA injection induced persistent inflammatory pain, which developed the anxiety-like behavior 3 weeks after CFA injection. It is consistent with the studies reported previously (27, 45). Notably, the chronic inflammatory pain may affect locomotor activity.…”
Section: Discussionsupporting
confidence: 94%
“…Like the anxiogenic effect of neuropathic pain (43, 44), CFA injection induced persistent inflammatory pain, which developed the anxiety-like behavior 3 weeks after CFA injection. It is consistent with the studies reported previously (27, 45). Notably, the chronic inflammatory pain may affect locomotor activity.…”
Section: Discussionsupporting
confidence: 94%
“…Clinical 57,81,84 and preclinical 40,41,49,62,74,90 studies have indicated strong comorbidity between chronic pain and anxiety. Furthermore, clinical studies have shown that CBD is effective at reducing anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…A study using a rat model with a chronic constriction injury reported that long-term pain led to an anxiety-like profile, increased responses to aversion, and impairments in cognitive tasks [39]. Wu et al reported that negative effects including pain aversion and anxiety were associated with hyperalgesia but that the manifestations of negative effects may occur over different time courses, suggesting that therapy should be targeted based on the different stages of pain and its comorbidities [40].…”
Section: Pain and Negative Affective Statesmentioning
confidence: 99%